Working Together to Move Client Relationships from Advice to Partnership in Sustainable Energy Finance - Beloe, William (World Bank, Washington, DC, 2012)
International Finance Corporation (IFC) has successfully developed sustainable energy projects in a number of emerging markets over the last decade. While each intervention is tailored to its specific markets and the needs of clients, in general the initiatives have focused on using local financial intermediaries as aggregating agents to stimulate investment in both energy efficiency and renewable energy, thus reducing both client operating costs (and improving the clients' margins) and greenhouse gas emissions. This paper focuses on the sustainable energy finance project IFC has developed in the Philippines and how author have leveraged more developed projects and ensured a one-IFC approach, the importance of focused research, listening to and being responsive to clients, and maintaining flexibility and realistic objectives in the program design. This document is intended for IFC colleagues responsible for developing projects in various business lines and regions, with particular relevance to those involved with either sustainable energy or local financial institutions. The lessons are presented with minimum technical jargon to make the message accessible to as wide an audience of project/program developers as possible.